COMPREHENSIVE GC-MS METHOD FOR THE ESTIMATION OF EXTRACTABLE ORTHO-PHENYLPHENOLS (OPPS) CONTENTS IN TEXTILE AND LEATHER TEST SPECIMENS (International Journal of NeuroOncology and Therapeutics, 2025)
A new method was established for determination of extractable ortho-phenylphenol (OPP) contents, its salts and esters in textile and leather test specimens. 0.1 M potassium hydroxide assisted with ultrasonic bath was used for alkaline digestion of test specimens. Test specimens were acetylated using acetic anhydride assisted with mechanical shaker at 200 rpm for 60 mins time. OPP contents were extracted in n-Hexane and were analyzed using fused silica capillary HP-5MS column. Helium gas 99.9 % purity was used as mobile phase. One target and two qualifier ions were selected for target analyte in GC-MS under selective ion monitoring (SIM) mode. Pre-treatment parameters as extraction method, solvent and time were optimized. Under optimized conditions recovery of standard was in the range of 93 to 98 %. Linearity was with regression value 0.9993-0.9995. Calibration curve working range was 0.1-5.0 mg L-1. Relative standard deviation (RSD) was up to 10% for test specimens and 5% for pure standards. Limit of detection was up to 0.006 mg L-1 level. From actual test specimens OPP contents were successfully analyzed using developed analytical method. OPP contents found were 1.15 to 35.52 mg L-1.